Child beliefs, societal beliefs, and teacher-student identity match. (August 2020) - Eble, Alex; Hu, Feng
Abstract: Children routinely benefit from being assigned a teacher who shares an identity with them, such as gender or ethnicity. We study how student beliefs impact teacher-student gender match effects, and how this varies across subjects with different societal beliefs about differential ability by gender. A simple model of belief formation yields two predictions: one, that match effects will be larger for students who believe they are of low ability, and two, that they will be greater in subjects where societal beliefs tell the child they are of low ability because of their membership in a given group, such as gender or race. We test these using data from Chinese middle schools, exploiting random assignment of students to teachers. In China, many people believe boys are innately better than girls at math. We find that being assigned a female math teacher helps low-perceived-ability girls and slightly harms low-perceived-ability boys, with no effects for other children. In English and Chinese – subjects where societal beliefs do not suggest boys are superior to girls – the effects of teacher-student gender match on low perceived ability girls diminish or disappear. This yields policy implications for the assignment of teachers to students.